Himalayan fermented beverages and their therapeutic properties with scientific validations: a comprehensive review - Soumya Majumder; Malay Bhattacharya (Journal of Ethnic Foods)
Abstract The Himalayan ethnoecology revolves around a balanced relationship between harsh mountain environment and the diverse lifestyles of its ethnic communities, where traditional knowledge on medicinal plants and fermented foods plays important role in their survival strategies. At high-altitudinal cold temperature and hypoxic condition, Himalayan tribal communities opt for easily digestible pre-digested foods rich in nutrients. Lack of suitable conditions for agriculture, the remoteness of the settlements, poor transportation systems, and limited availability of raw materials throw challenges to the agriculture and food production in the Himalayas which necessitate food preservation to extend shelf life. Thus, fermentation process is carried out to extend the shelf life of a food rather than just alcohol production. Chhang, soor, tongba, jaanr, raksi, apong, yu, zutho, judima, chu, qingke, ara, etc., are traditionally fermented beverages consumed in the Himalayan regions for relaxation which also offer health benefits. These ethnic beverages are often fortified with ethnomedicinal natural products native to the Himalayas which help inhabitants and tourists in coping with altitude-related stresses and acclimatizing to the region's climate. This review work begins with a background unfolding various altitudinal stresses on human health in Himalaya’s perspective and continues with an investigation into the scientifically proven benefits of traditional fermented beverages. There is a pile of document that reports surveyed secondary data on identification of region specific starters and beverages, ethnobotanic preparations and ethnomedicinal claims of antioxidant, anti-inflammatory, antimicrobial, gastrointestinal-protective, rejuvenating and altitude-sickness healing properties. This review article identified the limited volume research on nutraceutical values of the Himalayan fermented beverages and described scientific validations of the ethnomedicinal claims through biochemical characterization, ethno-microbiology and metabolomics.